The Lexical Cohesion Found in the Educational Article of Jakarta Post - Nenni Triana Sinaga; Hotmian Sagala; Uli Evianna Hutabarat; Joel Apriadi Sinaga; Johannes Nababan (Pioneer: Journal of Language and Literature, 2022)
The article writing found in the Jakarta post is essential to understand, especially in learning English and to know the quality of the article. This study aimed to determine what type of lexical cohesion is most prevalent in Jakarta Post educational articles and why that type of lexical cohesion is prevalent in the first place. The researcher used Halliday and Hassan's theories about lexical cohesion, which is lexical cohesion divided into two kinds, namely reiteration and collocation. There are five types of reiteration: repetition, synonymy, antonym, meronym, and hyponym. This study was conducted using the qualitative method. Data analysis used Miles and Huberman's model (reduction, display, and verification). The outcomes were discovered. Repetition occurred in nine items, synonymy in five items, hyponymy in an item, antonym in an item, meronym in an item, and collocation in five items. The most dominant kind that was found is repetition, with nine items. It is more dominantly found in educational articles because the article shows the quantity of affirmation of ideas or intensity and beauty in clarifying the contents of the text.